Establishing a Fiscal Risk Management Department in the Ministry of Finance of Serbia - World Bank (World Bank, Washington, DC, 2017)
While current legislation in Serbia covers some fiscal risks and some aspects of how to manage them, important gaps remain in the country’s fiscal risk management framework. Based on discussions at a workshop on fiscal risk management held in Serbia in March 2016, stakeholders from across the government have agreed on the need to establish a Fiscal Risk Management Department (FRMD) within the Ministry of Finance. The stated objective of the new department would be to strengthen fiscal risk management and coordination across the government. Specifically, the responsibilities of the department would include (i) ensuring that fiscal risks are properly identified, quantified, monitored, mitigated, and disclosed, and collecting all available information and analysis relevant for fiscal risk management; (ii) providing advice to the minister of finance on issues of fiscal risk and recommending actions to mitigate risks; and (iii) coordinating all government entities that are involved in or relevant for fiscal risk management